PENGARUH PENDIDIKAN KESEHATAN TENTANG PEMERIKSAAN PAYUDARA SENDIRI (SADARI) TERHADAP PENGETAHUAN REMAJA PURTI SEBAGAI DETEKSI DINI KANKER PAYUDARA DI SMAN 5 KOTA TANGERANG SELATAN - Susilawati; Ristiyanah (STIKes IMC Bintaro, 2019)
Breast cancer is the second leading cause of death in women after cervix cancer, more than 1.5 million women die every year. This can be prevented by modifying the risk factors the causes of cancer and one of the effective ways to prevent breast cancer is to do a breast self examination (BSE) that can suppress mortality. The goal in this research is to know the effect of health education On breast self Examination (BSE) on the female students knowledge of early detection of breast cancer. Type of this research is Quantitative Research with Quasi Experimental Design One Group Pretest-Post Test. Instrument used for knowledge is the questionnaire. The population of the research was the female students SMAN 5 South Tangerang city. The technique of sampling using Random Sampling with a total sample of 189 respondents. Data analysis using the method of test for Paired Samples T Test. The results of the analysis before and after a test of Paired Samples T Test pointing right p value of 0.000 knowledge with the default p value < 0.05. Conclusion: there is an influence of knowledge before and after health education.